DAMPAK PEMEKARAN TERHADAP PEMBANGUNAN DAERAH DI KECAMATAN PEKAITAN KABUPATEN ROKAN HILIR TAHUN 2010-2012 - Andi Rakasiwi; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
service to the community. With the expansion in the area expect an every community needs thatmust be fulfilled by the government can be identified and coordinated in accordance with theirrespective potentials. However, if viewed from the concept, the role of local government is toprovide public services. Accompanying the political dynamics that have developed since thebeginning of the reform era, especially with regard to the enactment of Law No. 22 of 1999sprung the desire of various regions to split away to form new autonomous regions. For thegovernment issued Government Regulation No. 129 of 2000 on Regional Expansion governing,among others, about the procedural instruments and instrument requirements of regionalexpansion. and Government Regulation (PP) No. 19 of 2008 on government enacted the District.The main purpose Pekaitan the District Redistricting is